Jawapan

  • Pengguna Brainly
2016-01-19T16:48:09+08:00
1. 2x^2 - 7x + 4 = 0
    x = 2.781 , x = 0.7192

2. - x^2 - 12x + 9 = 0
    x^2 + 12x - 9 = 0
    x = 0.7082 , x = - 12.71
1 5 1
2016-01-21T23:17:44+08:00
1) 2x^2 - 7x + 4 = 0
x^2 - 7x/2 + 4/2 = 0
x^2 - 7x/2 + 2 = 0
x^2 -7x/2 = -2
x^2 - 7x/2 + (-7/2 bahagi 2)^2 = -2 + (-7/2 bahagi 2)^2
x^2 -7x/2 + (-7/4)^2 = -2 + 49/16
(x - 7/4)^2 = 17/16
x - 7/4 = √(17/16)
x - 7/4 = +-1.0308

x - 7/4 = 1.0308
x = 1.0308 + 1.75
x = 2.7808

x - 7/4 = -1.0308
x = -1.0308 + 1.75
x = 0.7192

2) -x^2 - 12x + 9 = 0
x^2 + 12x - 9 = 0
x^2 + 12x = 9
x^2 + 12x + (12/2)^2 = 9 + (12/2)^2
x^2 + 12x + (6)^2 = 9 + 36
(x + 6)^2 = 45
x + 6 = √45
x + 6 = +-6.7082

x + 6 = 6.7082
x = 0.7082

x + 6 = -6.7082
x = -12.7082